Age-associated B cells contribute to the pathogenesis of rheumatoid arthritis by inducing activation of fibroblast-like synoviocytes via TNF-α-mediated ERK1/2 and JAK-STAT1 pathways. Issue 11 (27th June 2022) - Qin, Yi; Cai, Ming-Long; Jin, Hui-Zhi; Huang, Wei; Zhu, Chen; Bozec, Aline; Huang, Jingang; Chen, Zhu
Abstract : Objectives: Age-associated B cells (ABCs) are a recently identified B cell subset, whose expansion has been increasingly linked to the pathogenesis of autoimmune disorders. This study aimed to investigate whether ABCs are involved in the pathogenesis and underlying mechanisms of rheumatoid arthritis (RA). Methods: ABCs were assessed in collagen-induced arthritis (CIA) mice and patients with RA using flow cytometry. Transcriptomic features of RA ABCs were explored using RNA-seq. Primary fibroblast-like synoviocytes (FLS) derived from the synovial tissue of patients with RA were cocultured with ABCs or ABCs-conditioned medium (ABCsCM). IL-6, MMP-1, MMP-3 and MMP-13 levels in the coculture supernatant were detected by ELISA. Signalling pathways related to ABCs-induced FLS activation were examined using western blotting. Results: Increased ABCs levels in the blood, spleen and inflammatory joints of CIA mice were observed. Notably, ABCs were elevated in the blood, synovial fluid and synovial tissue of patients with RA and positively correlated with disease activity. RNA-seq revealed upregulated chemotaxis-related genes in RA ABCs compared with those in naive and memory B cells. Coculture of FLS with RA ABCs or ABCsCM led to an active phenotype of FLS, with increased production of IL-6, MMP-1, MMP-3 and MMP-13. Mechanistically, ABCsCM-derived TNF-α promoted the upregulation of interferon-stimulated genes in FLS, with elevated phosphorylation of ERK1/2 and STAT1. Furthermore, blockage of ERK1/2 and Janus Kinase (JAK)-STAT1 pathways inhibited the activation of FLS induced by ABCsCM. Conclusions: Our results suggest that ABCs contribute to the pathogenesis of RA by inducing the activation of FLS via TNF-α-mediated ERK1/2 and JAK-STAT1 pathways.